Dual Cross-Linked Chitosan-Based Films with pH-Sensitive Coloration and Drug Release Kinetics for Smart Wound Dressings - Jongjit Chalitangkoon; Arnat Ronte; Tanaporn Sintoppun; Nuttaporn Manapradit; Pathavuth Monvisade (ACS Omega, 2025)
In this study, we developed dual-cross-linked hydrogel films based on carboxyethyl chitosan (CECS) and sodium alginate (SA), utilizing dialdehyde β-cyclodextrin (DA-βCD) and gluconic acid δ-lactone (GDL) as cross-linkers. Designed as smart wound dressings, the films exhibit pH sensitivity due to the incorporation of carboxyethylated phenol red-grafted chitosan (CS-PR-AA), which allows them to change color from orange to purple in response to pH variations. FT-IR and TGA analyses confirmed the formation of imine bonds and polyelectrolyte complexes, indicating successful cross-linking. The films demonstrated high cell viability, confirming their biocompatibility and nontoxicity. The swelling behavior varied with pH, underscoring their adaptability to different wound environments. Additionally, drug release kinetics were studied for films incorporating diclofenac sodium (DCF) at various pH levels, revealing that the release rate was influenced by cross-linking density and environmental pH. These findings suggest that the dual-cross-linked hydrogel films have significant potential as smart wound dressings, offering controlled drug release and pH-responsive behavior suitable for wound care applications.
Keywords: Hydrogels: synthesis, properties, applications; Antimicrobial agents and applications; Wound Healing and Treatments